2021
DOI: 10.18632/aging.202390
|View full text |Cite
|
Sign up to set email alerts
|

The roles of PARP-1 and XPD and their potential interplay in repairing bupivacaine-induced neuron oxidative DNA damage

Abstract: Bupivacaine has been widely used in clinical Anesthesia, but its neurotoxicity has been frequently reported, implicating cellular oxidative DNA damage as the major underlying mechanism. However, the mechanism underlying bupivacaine-induced oxidative DNA damage is unknown. We, thus, exposed SH-SY5Y cells to 1.5mM bupivacaine to induce neurotoxicity. Then, iTRAQ proteomic analysis was used to explore the repair of neuronal oxidative DNA damage. By analyzing the STRING version 11.0 database, the bioinformatics re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In response to oxidative DNA damage, numerous DNA repair enzymes and multiple repair pathways are required to maintain genomic integrity [ 22 ]. Proteomics and other studies have shown that nucleic acid excision repair (NER) plays a key role in bupivacaine-medicated neuronal DNA repair [ 23 ]. PARP-1 is a multidomain and multifunctional nuclear enzyme regulating chromatin structure and transcription.…”
Section: Resultsmentioning
confidence: 99%
“…In response to oxidative DNA damage, numerous DNA repair enzymes and multiple repair pathways are required to maintain genomic integrity [ 22 ]. Proteomics and other studies have shown that nucleic acid excision repair (NER) plays a key role in bupivacaine-medicated neuronal DNA repair [ 23 ]. PARP-1 is a multidomain and multifunctional nuclear enzyme regulating chromatin structure and transcription.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of the vital repair enzyme XPD was increased, and this enzyme participated in repairing oxidative DNA damage ( Figure 2 ). Our previous study [ 18 ] also suggested that XPD participates in repairing oxidative DNA damage caused by bupivacaine in neurons. Therefore, XPD may be the most critical restriction enzyme in NER, the primary DNA repair pathway in mammalian cells [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 95%
“…The comet assay was used to detect DNA damage in individual cells as previously described [ 18 ]. Briefly, the SH-SY5Y cells were plated in 12-well plates, and the extent of DNA damage was measured by the kit (Trevigen's Comet Assay® Kit) following manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For experimental conditions, SH-SY5Y cells were maintained in a humidified incubator with 5% CO2 at 37°C. Four different groups were assigned for the experimental protocol: 1. control group, 2. capsaicin group (5,10,20,40,80, and 100 μM), 3. bupivacaine group (0.1, 0.5, 1, 2, 2.5, and 5 mM), 4. capsaicin + bupivacaine group (Cells exposed to capsaicin at concentrations of 2.5, 5, and 10 µM for 24 hours were then treated with bupivacaine (1 mM) for 2 hours. XTT test reagent was added to the groups whose incubation times were completed, and absorbance measurements were made by means of a spectrophotometer (Thermo, Germany) at 450 nm.…”
Section: Xtt Assaymentioning
confidence: 99%